JALOLIDDIN MANGUBERDI'S TACTICS AGAINST THE MONGOLS ARMY (Academicia Globe: Inderscience Research, 2023)
In this article, Jalaluddin Manguberdi, a great general and statesman, who showed great heroism during the Mongol invasion, defeated the Mongols several times and was recognized by Genghis Khan with his invincibility historical heroes are mentioned.